Executive Functions During Submaximal Exercises in Male Athletes: Role of Blood Lactate - Coco, Marinella; Buscemi, Andrea; Cavallari, Paolo; Massimino, Simona; Rinella, Sergio; Tortorici, Marta Maria; Maci, Tiziana; Perciavalle, Vincenzo; Tusak, Matej; Di Corrado, Donatella; Perciavalle, Valentina; Zappalà, Agata (Frontiers in Psychology, 2020)
The present study was carried out among 20 healthy young male athletes to determine whether aerobic exercise performed at two different intensities is able to affect executive functions. For this purpose, we used the Stroop Color Word Test (SCWT) to evaluate the ability to inhibit cognitive interference and the Trail Making Test (TMT) to assess organized visual search, set shifting, and cognitive flexibility. Simple Reaction Time (RT), as a measure of perception and response execution, was also evaluated. The experimental protocol included the measure of blood lactate levels with the aim of assessing possible relations between lactate blood values and selected executive functions after a 30-min steady-state test performed at 60% and at 80% of VO2max. The results showed that a 30-min aerobic exercise is not associated with a worsening of executive functions as long as the blood lactate levels stay within the 4 mmol/l threshold.